2020
DOI: 10.1038/s41598-020-70253-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated structural and functional analysis of the protective effects of kinetin against oxidative stress in mammalian cellular systems

Abstract: Metabolism and signaling of cytokinins was first established in plants, followed by cytokinin discoveries in all kingdoms of life. However, understanding of their role in mammalian cells is still scarce. Kinetin is a cytokinin that mitigates the effects of oxidative stress in mammalian cells. The effective concentrations of exogenously applied kinetin in invoking various cellular responses are not well standardized. Likewise, the metabolism of kinetin and its cellular targets within the mammalian cells are sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Previous studies have demonstrated the anti-ageing, anti-inflammatory, immunomodulatory, and neuro-protective effects of kinetin in mammalian cells [ 20 , 21 , 22 , 23 ]. Despite the lack of understanding of its complete detailed biogenesis [ 22 ] or its targets in human cellular proteome and functional implications for mammalian cells [ 26 ], kinetin caught much attention recently for its potential therapeutic applications. One of the putative kinetin binding targets (KBP) is the adenosine receptor.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated the anti-ageing, anti-inflammatory, immunomodulatory, and neuro-protective effects of kinetin in mammalian cells [ 20 , 21 , 22 , 23 ]. Despite the lack of understanding of its complete detailed biogenesis [ 22 ] or its targets in human cellular proteome and functional implications for mammalian cells [ 26 ], kinetin caught much attention recently for its potential therapeutic applications. One of the putative kinetin binding targets (KBP) is the adenosine receptor.…”
Section: Resultsmentioning
confidence: 99%
“…These concordant results from docking, binding energy, and crystal structure validate the docking output and the notion that the adopted computational approach is working here correctly. In a previous study, we found multiple kinetin binding residues on the A2a-R receptor in a non-adenosine binding socket [ 26 ]. To get insight into the functional homology between kinetin and adenosine, we specifically focused on the adenosine binding sockets of the A2a-R receptor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations